Statherin-Derived Peptide Protects against Intrinsic Erosive Enamel Wear in situ - Taira, Even Akemi; Ferrari, Carolina Ruis; Carvalho, Gabriel; Pelá, Vinicius Taioqui; Ventura, Talita Mendes Oliveira; Crusca, Edson [UNESP]; Marchetto, Reinaldo [UNESP]; Buzalaf, Marília Afonso Rabelo (Karger Publishers, 2024)
Introduction: This in situ study investigated the protective effect of a solution containing statherin-derived peptide (StatpSpS) against enamel intrinsic erosion (ERO). Methods: Fifteen volunteers wore appliances containing 2 bovine specimens. The samples were subjected to ERO with HCl, mimicking dental ERO by intrinsic acid. The volunteers participated in 3 phases (double-blind and crossover): (1) deionized water (negative control); (2) commercial solution containing SnCl2/NaF/AmF (800 ppm Sn+2, 500 ppm F-, pH 4.5) (positive control); (3) solution containing 1.88 × 10-5 M StatpSpS. Four times a day, the volunteers administered one drop of the solutions (50 μL, 1 min) on each specimen. After the treatment, erosive challenges were performed extraorally with 0.01 M HCl (pH 2.0, 4 times/day, 1 min, 150 mL). Enamel wear was assessed by profilometry. Data were analyzed by one-way RM-ANOVA/Bonferroni s tests (p < 0.05). Results: In terms of the treatments, both the commercial solution (SnCl2/NaF/AmF) and StatpSpS significantly reduced the wear when compared to the negative control (p < 0.01), without significant differences between them (p > 0.05). Conclusion: The solution containing StatpSpS demonstrated protection against enamel intrinsic erosive wear. This study marks a significant advancement in the prevention of intrinsic erosive wear, utilizing StatpSpS in acquired pellicle engineering procedures.
Keywords: Acquired pellicle; Erosive tooth wear; Prevention; Statherin